Enhancing the 21st Century Learning Skills of HUMSS-11 Students Through Integrative Performance Task - Ramiscal, Joseph; Salanga, Maria Cristina; Pascual, Dennis (Journal of Interdisciplinary Perspectives, 2025)
The policy guidelines on the K to 12 basic education program state that students who graduate must become holistically developed Filipinos equipped with 21st-century learning skills, such as information, media, and technology skills; learning and innovation skills; communication skills; and life and career skills (Briones, 2019). The purpose of this study is to enhance the 21st-century learning skills of the HUMSS-11 students through the integrative performance task. Specifically, it aims to determine students' developmental needs in relation to 21st-century learning skills and to understand how an integrative performance task can enhance these skills. The study used document analysis to interpret the data from students' reflective essays in their portfolios. Based on the study's findings, grade 11 students have greater development needs in communication skills. However, it was also found that most of them have enhanced their communication skills in the integrative performance task, including their life and career skills. Overall, based on the grade 11 HUMSS students' reflective essays in their portfolios regarding their integrative performance task, most of them have enhanced their 21st-century learning skills, specifically in communication and life and career skills. This suggests that integrative performance tasks can help enhance learners’ 21st-century learning skills. These skills will help them prepare to survive in a complex world, become successful in life, and be productive citizens of their country.